2021
DOI: 10.1002/hyp.14026
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of vegetation dynamics in hydrologically connected wetlands caused by dam operation

Abstract: The dynamic responses of wetlands to upstream water conservancy projects are becoming increasingly crucial for watershed management. Poyang Lake is a dynamic wetland system of critical ecological importance and connected with the Yangtze river. However, in the context of disturbed water regime in Poyang Lake resulting from human activities and climate change, the responses of vegetation dynamics to the Three Gorges Dam (TGD) have not been investigated. We addressed this knowledge gap by using daily water level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The study of Lin et al (2023) found that the area of wetland vegetation in Poyang Lake has increased to a certain extent and expanded to the centre of the lake since 2000. Moreover, Zheng et al (2021) compared the vegetation coverage of Poyang Lake wetland before and after the operation of the TGR, and found that the vegetation growth rate accelerated after 2003. Han et al (2018) revealed that the area of Carex cinerascens , Phalaris arundinacea ‐ Polygonum hydropiper and Phragmites australis ‐ Triarrhena lutarioriparia communities in Poyang Lake wetland had an obvious increasing trend from 2000 to 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Lin et al (2023) found that the area of wetland vegetation in Poyang Lake has increased to a certain extent and expanded to the centre of the lake since 2000. Moreover, Zheng et al (2021) compared the vegetation coverage of Poyang Lake wetland before and after the operation of the TGR, and found that the vegetation growth rate accelerated after 2003. Han et al (2018) revealed that the area of Carex cinerascens , Phalaris arundinacea ‐ Polygonum hydropiper and Phragmites australis ‐ Triarrhena lutarioriparia communities in Poyang Lake wetland had an obvious increasing trend from 2000 to 2014.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, there have been many flood events in the YRB, causing serious loss to life and property (e.g., Figure 2) [34]. The flood disaster situation in the YRB has been alleviated only by the construction of the Three Gorges Dam [35]. This study divides the YRB into 12 sub-basins according to the classification criteria of the Ministry of Water Resources of the People's Republic of China (e.g., Figure 1 and Table 1).…”
Section: Study Areamentioning
confidence: 99%
“…In the past, there have been many flood events in the YRB, causing serious loss to life and property (e.g., Figure 2) [34]. The flood disaster situation in the YRB has been alleviated only by the construction of the Three Gorges Dam [35]. Taihu Lake Rivers Basin TLRB…”
Section: Study Areamentioning
confidence: 99%
“…The Three Gorges Dam (TGD) in the upstream of the Yangtze River is the world's largest dam and remains one of the most controversial projects in China. Previous studies showed that TGD operation, which began in 2003, has significantly changed the hydrological rhythm downstream (Zhang et al, 2015;Wang et al, 2019;Peng et al, 2020;Zheng et al, 2021). For example, Zhang et al (2015) found that the waterflow from downstream lakes connected to the Yangtze River has increased by 57 billion m 3 as compared with that during pre-TGD period.…”
Section: Introductionmentioning
confidence: 99%